2002
DOI: 10.1002/pola.10281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salts and copolymer composition on the lower critical solution temperature of poly(methyl 2‐acetamidoacrylate‐co‐methyl methacrylate) solutions

Abstract: Copolymerizations of methyl 2‐acetamidoacrylate (MAA) with methyl methacrylate (MMA) were carried out at 60 °C in chloroform. Copolymers containing MAA units in the range of 83–90 mol % exhibited a lower critical solution temperature (LCST), although homopolymers of MAA and MMA did not. The LCST of polymer solutions decreased with (1) an increase in the concentration of the copolymer, (2) a decrease in the MAA content in the copolymer, and (3) an increase in the concentration of salts added. The effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
6
16
0
Order By: Relevance
“…According to the type and concentration of ions, this hydration sheath will be more or less destructured (in case of “salting‐out” ions) or strengthened (in case of “salting‐in” ions) . The lowering of LCST (salting‐out effect) observed is nearly a linear function of the metal ion concentration, supporting the observation found in the literature . The observed “salting‐out” process can be explained as a combination of several effects (i.e., changes of the water structure in the polymer hydration sheath and changes of the interactions between the polymer and the solvent, due to the presence of metal ion/salts) .…”
Section: Resultssupporting
confidence: 84%
“…According to the type and concentration of ions, this hydration sheath will be more or less destructured (in case of “salting‐out” ions) or strengthened (in case of “salting‐in” ions) . The lowering of LCST (salting‐out effect) observed is nearly a linear function of the metal ion concentration, supporting the observation found in the literature . The observed “salting‐out” process can be explained as a combination of several effects (i.e., changes of the water structure in the polymer hydration sheath and changes of the interactions between the polymer and the solvent, due to the presence of metal ion/salts) .…”
Section: Resultssupporting
confidence: 84%
“…Therefore, both mechanisms account for the decrease in the CFT values of the temperature sensitive polymers obtained in this study. Figures show that the lowering of CFT is a linear function of the salt concentration, supporting the observations found in the literature by different authors 61–64. The changes in the CFT values, which are caused by the addition of sodium chloride, can be explained with salting‐in effect 64.…”
Section: Resultssupporting
confidence: 88%
“…In addition, recent contribution reported in the literature highlighted the higher complexity of the salt effect 33 and concluded that direction and magnitude of the salt effect depended on both the nature of the ion and the nature of the polymer. For instance, it is important to notice that, in the case of poly(methyl 2acetamidoacrylate-co-methyl methacrylate), a slight augmentation of the LCST was noticed in the presence of NaNO 3 while with NaCl temperature led to a linear decreasing, with a salt concentration ranging from 0 to 0.6 mol.L -1 , 34 which was in accordance with our results. The effect of the cations was also considered using lithium, potassium, and sodium chloride (Fig.…”
Section: Influence Of Salts and Acidity On The Cloud Pointssupporting
confidence: 93%